2008
DOI: 10.1002/dneu.20614
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging methods for assessing fetal brain development

Abstract: Fetal magnetic resonance imaging provides an ideal tool for investigating growth and development of the brain in vivo. Current imaging methods have been hampered by fetal motion but recent advances in image acquisition can produce high signal to noise, high resolution 3-dimensional datasets suitable for objective quantification by state of the art post acquisition computer programs. Continuing development of imaging techniques will allow a unique insight into the developing brain, more specifically process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 47 publications
1
49
0
Order By: Relevance
“…Currently, mainly the brain and the whole fetus appearance are qualitatively examined in clinical practice [1,2]. Fetal motion and its unpredictable nature ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, mainly the brain and the whole fetus appearance are qualitatively examined in clinical practice [1,2]. Fetal motion and its unpredictable nature ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The application of modern diffusion tensor imaging (DTI) allows the in-vivo analysis of abnormal changes of the axonal pathways during vulnerable periods (Huang et al 2006(Huang et al , 2009Kasprian et al 2008;Kim et al 2008;Rutherford et al 2008;Aeby et al 2009;Hoon et al 2009;Ment et al 2009;Ramenghi et al 2009). It has been shown that the DTI technique is very useful for the 3D study of the macroscopic fiber bundle architecture and their maturational changes.…”
Section: Introductionmentioning
confidence: 99%
“…15 Perhaps the most distinguishing characteristics of fetal head motion are that it is 3D and uncontrollable. 16,17 In some centers, maternal sedation is used to try to suppress fetal motion. However, even if the fetus remains still, head motion may occur, depending on fetal life (eg, in breech presentation, where the head lies close to maternal diaphragm and maternal respiratory motion is directly transmitted to fetal head).…”
Section: Fetal Motionmentioning
confidence: 99%